2020
DOI: 10.3389/fimmu.2020.00667
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immune Responses in HELLP Syndrome

Abstract: Innate and adaptive immune involvement in hemolysis, elevated liver enzymes and low platelet (HELLP) syndrome is an understudied field, although it is of high clinical importance. This syndrome implies a risk of serious morbidity and mortality to both the mother and the fetus during pregnancy. It was proposed that HELLP syndrome occurs in a circulatory inflammatory milieu, that might in turn participate in a complex interplay between the secreted inflammatory immunomodulators and immune cell surface receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 148 publications
0
17
0
3
Order By: Relevance
“…Therefore, additional and more specific/sensitive detection criteria are needed for improving PE and HELLP screening, diagnosis and treatment. In recent years, various studies have shown that insufficient adaptations of the maternal immune system are implicated in the pathophysiology of PE and HELLP, including alterations in levels and function of regulatory T cells 17–19 . The B7 homolog 4, B7‐H4, is a member of the B7 family that was independently discovered by a number of scientists in 2003 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additional and more specific/sensitive detection criteria are needed for improving PE and HELLP screening, diagnosis and treatment. In recent years, various studies have shown that insufficient adaptations of the maternal immune system are implicated in the pathophysiology of PE and HELLP, including alterations in levels and function of regulatory T cells 17–19 . The B7 homolog 4, B7‐H4, is a member of the B7 family that was independently discovered by a number of scientists in 2003 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto, estudos genéticos sobre a hereditariedade da predisposição para préeclâmpsia e/ou síndrome HELLP na gravidez, provaram que fatores genéticos e imunológicos desempenham um papel importante na patogênese dessas afecções (STOJANOVSKA;ZENCLUSSEN, 2020).…”
Section: Desenvolvimentounclassified
“…HELLP syndrome occurs mostly in the second and third trimesters of pregnancy (usually between 27 and 7 weeks antenatally), and 15–30% of women present in the puerperium (usually within 7 days after delivery) ( 4 ). The pathological mechanism of the disease is not yet very clear, which may be related to placental origin ( 5 ), autoimmunity ( 6 ), mutations in coagulation factor V gene ( 7 ), fatty acid oxidation disorder symptoms ( 8 ) and so on. The incidence of HELLP syndrome is relatively low, accounting for only 0.5–0.9% of the pregnant population (the incidence in China can be about 2.5%), but the clinical manifestations are diverse, the disease develops rapidly, and poses a greater risk to maternal and child health, and the lives of mothers and children are often endangered by delayed treatment, with a high rate of maternal and child complications and death ( 9 ).…”
Section: Introductionmentioning
confidence: 99%